PERANCANGAN SISTEM INVENTORI BARANG BERBASIS WEB PADA RAPHAEL’S DIVAN - Adi Prayitno; M. Irham (Jurnal Publikasi Teknik Informatika, 2023)
Raphael's Divan is a company engaged in the furniture sector. In addition to selling furniture, Raphael's Divan also produces furniture, namely divans. Currently, data collection and report generation at Raphael's Divan is still done manually, so data information still has many shortcomings such as inappropriate stock of goods, lack of time efficiency, and data redundancy. Looking at the problems in Raphael's Divan, an inventory system application was made using the Prototype development method. This web-based inventory system application in its design uses HTML, PHP, Java Script and for the database it uses MySQL. The creation of a web-based inventory information system application aims to increase the effectiveness in data collection, reporting and information availability of goods, specifically raw materials in Raphael's Divan.